Sheikh Abdul Qadir Jilani Epitome of Islamic Propagation and Tasawuf - Ali, Damsaz (International Multidisciplinary Research Journal, 2011)
Devotion to God constituted the ideal life for Syed Abdul Qadir Jilani. People were constantly advised by him to reform their own thinking and conduct. He says one should always love God in the true sense and the most important kind of worship is to help the poor, the needy and to feed the hungry. As a result all were influenced by his teachings and above all their was moral correctness of people.Syed never in his life attached importance to material power and wealth. His much emphasis was on piety, simplicity, lawful earning and service to mankind. Corresponding Author: Ph.D.Scholar, Department of History, Research Unit, School of Social Sciences, Indira Gandhi National Open University (IGNOU), Maidan Garhi, New Delhi-110068, India